Peluang Dan Ancaman Perdagangan Bebas Antara Indonesia Dan Mercosure - Mohammad Rasyah Aufa Humaedi; Muhammad Rizki Erlangga Putra; Arindra Nurlaila Augustina; Abdurrahman Mubarok; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
Indonesia has established distinct and positive relationships with various Latin American countries. Numerous efforts have been made to explore participation, including with MERCOSUR (comprising Brazil, Argentina, Paraguay, and Uruguay). The member countries of MERCOSUR represent a viable business sector for Indonesian commodities. The objectives of this study are: (1) to understand the implementation of the Indonesia-MERCOSUR exchange, (2) to describe the factors influencing Indonesian commodities with MERCOSUR, and (3) to determine the techniques for participating in the Indonesia-MERCOSUR exchange. The logical strategies used are: Subjective Examination, Gravity Model, and SWOT Analysis. The performance of trade between Indonesia and MERCOSUR indicates that the value of Indonesian exports and imports with MERCOSUR is slightly lower compared to its competitors. Import duties imposed by MERCOSUR countries on essential Indonesian goods are still relatively high, while import duties imposed by Indonesia on essential MERCOSUR goods are quite low. The assessment results of the Gravity Model show that Indonesian products to MERCOSUR are significantly and fairly influenced by the Gross Domestic Product of MERCOSUR countries. The proposed strategies for future trade participation include: (a) enhancing Indonesia's capability to meet the MERCOSUR market, particularly for products such as palm oil, rubber, vehicle engine parts, synthetic yarn, footwear, coconut, and tobacco, (b) expanding serious trade cooperation with MERCOSUR countries as a Deregulation Region (FTA), (c) further developing the structure of tariffs and non-duty barriers between Indonesia and MERCOSUR, and (d) expanding Indonesia-MERCOSUR financial policies.